The cytokine response in THP-1 (monocyte) and HL-60 (neutrophil-differentiated) cells infected with different genotypes of Helicobacter pylori strains - Çalışkan, Reyhan; Sayı Yazgan, Ayça; Tokman, Hrisi Bahar; Sofyalı, Emre; Erzin, Yusuf Ziya; Akgül, Özer; Kurt, Aykut; Kalaycı, Fatma; Ziver, Tevhide; Yüksel, Pelin; Bal, Kadir; Kocazeybek, Bekir (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Helicobacter pylori (H. pylori) is a microaerophilic bacterium related with peptic ulcer and gastric cancer. Its virulence factors include cytotoxin-associated gene A (CagA) and vacuolating cytotoxin gene A (VacA) proteins. Cytokine release inducted by H. pylori colonization has an important role in pathogenesis of H. pylori. The severity of gastric pathologies depends on the H. pylori genotypes found in different geographical regions. We aimed to determine the relationship between different H. pylori genotypes and their effects on the cytokine release levels. Materials and Methods: ureC, cagA, vacAs1/s2, vacAm1/m2, and blood group antigen-binding adhesion protein A2 (babA2) virulence related genes were investigated in 21 H. pylori strains. Genotyping of 21 strains were made due to the presence of cagA, vacAs1/s2, vacAm1/m2, and babA2 genes. The H. pylori strains were cultured together with THP-1 and neutrophil-differentiated Human promyelocytic leukemia cells (HL-60) cells. The levels of cytokines interleukin (IL)-1β, IL-6, IL-8, IL-12, tumor necrosis factor-alpha (TNF-α), and IL-10 in these cells were measured after co-culturing with H. pylori strains. Results: The following five different genotypes were detected: Genotype1: cagA and vacAs1m2; Genotype2: cagA and vacAs1m1; Genotype3: cagA, vacAs1m2, and babA2; Genotype4: vacAs2m2; and Genotype5: cagA and vacAs2m2. All these genotypes significantly induced the levels of IL-1β, IL-6, IL-8, IL 10, and TNF-α in THP-1 cells. Genotype 5 caused higher amounts of IL-1β, IL-6, TNF-α, and IL-10, whereas genotype 1 induced the highest levels of IL-8. In neutrophil-differentiated HL-60 cells, genotype 4 increased IL-6 levels and genotype 3 and 4 elevated IL-8 levels significantly. Conclusion: These results suggested that cytokine response of the host varies depending on the specific immune response of the host against different H. pylori strains.